Penerapan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah pada Usaha Umkm Bubur Bayi Nice - Awalita Ariyani Sujarno; Maria Yovita R Pandin (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The background to this research is that there is a problematic situation in recording financial reports, because the system for recording financial reports in MSMEs has not recorded financial reports based on Financial Accounting Standards (SAK). The financial condition of micro, small and medium enterprises in this research needs to be analyzed in order to find out how far the financial condition has developed. The aim of this research is to find out how the finances of Nice Baby Porridge UMKM are recorded, how accounting is recorded based on accounting principles and how to apply financial reports based on SAK EMKM. The method in this research is data collection in compiling this research including observation. interviews and documentation The results of this research are that the Nice Baby Porridge UMKM has not implemented financial reports in accordance with SAK EMKM due to limited knowledge.